Therapist and Client Discussions of Drinking and Coping: A Sequential Analysis of Therapy Dialogues in Three Evidence-Based Alcohol Use Disorder Treatments - Magill, M. (Addiction, 2016)
BACKGROUND AND AIMS: Research into the active ingredients of behavioral interventions for alcohol use disorders (AUD) has focused on treatment-specific factors often yielding disappointing results. The present study examines common factors of change in motivational enhancement therapy, cognitive-behavioral therapy, and twelve-step facilitation therapy by 1) estimating transitional probabilities between therapist behaviors and subsequent client Change (CT) and Sustain (ST) Talk and 2) examining therapist skillfulness as a potential predictor of transition probability magnitude. DESIGN: Secondary data analysis examined temporal associations in therapy dialogues. SETTING: USA: data were from Project MATCH (1997). PARTICIPANTS: N = 126 participants who received Motivational Enhancement Therapy, Cognitive-Behavioral Therapy, or Twelve-Step Facilitation Therapy. MEASUREMENTS: Therapist behaviors were measured in three categories (Exploring, Teaching, Connecting) and client statements included five categories (CT-Distal, ST-Distal, CT-Proximal, ST-Proximal, Neutral). Therapist skillfulness was measured using a 5-point ordinal scale. FINDINGS: Relative to chance, therapist exploratory behaviors predicted subsequent client discussion of distal, drinking behavior (OR = 1.37 to 1.78, p < .001) while suppressing discussion of proximal coping and neutral content (OR = .83 to .90, p < .01). Unexpectedly, therapist teaching suppressed distal drinking language (OR = .48 to .53, p < .001) and predicted neutral content (OR = 1.45, p < .001). Connecting behaviors increased both drinking and coping language, particularly language in favor of change (CT OR = 1.15 to 1.84, p < .001). Analyses of exploring and connecting skillfulness revealed that high skillfulness maximized these behaviors effect on client responses, but not teaching skillfulness. CONCLUSIONS: In motivational enhancement therapy, cognitive-behavioral therapy, and twelve-step facilitation therapy for alcohol use disorders, the therapists who explore and connect with clients appear to be more successful at eliciting discussion about change then therapists who engage in teaching behavior. Therapists who are more skilled achieve better results than those who are less skilled.